LA DYNAMIQUE AGRICOLE ET LES MUTATIONS SPATIALES DANS LA COMMUNE DE M’BATTO - Atta Koffi; Gogbe Téré; Kakou Golly Mathieu (European Scientific Journal, ESJ, 2013)
Situated in the Centre-East of Ivory Coast, the town of M’Batto like the other town of the country knew a population and economic growth, which created a change in its urban space. A town which economy is strongly influenced by its agriculture. In this way, the other economic sectors are firmly linked to it.Thus, from 1960 to 1980, M’Batto knew a legendary prosperity due to the high price of the binomial coffee-cocoa, considered as “the teats” of the Ivorian economy on the international markets. Nicknamed in local language “M’Batto sika-boutou”, which means the money, is poured on the ground, that town knew a strong spatial transfer from the urban point of view, thanks to the incomes from the agriculture.The town of M’Batto is the type of town, which combined its destiny with agriculture. The consequence of that situation was the spatial dynamic that knew M’Batto from 1960-1980, with more than 27% as urbanization rate.From 1980till now, the cocoa loop moved from the East of the country to the West. From then on, M’Batto has been living an agricultural crisis, which has also affected its urban space. The spatial dynamic of M’Batto depended on the wealth of its rural environment, base of the agricultural prosperity.In that agricultural town, more than 85% of the houses belong to the native farmers. It is for them an evident will to see their living space change by their deliberate actions, because for Agni people building a house in hard in a confirmation of his personality.